Synthesis of New Organic Compounds Via Three Components Reaction with Studying of (Identification ,Thermal Behavior, Bioactivity on Bacteria of Teeth) - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
All compounds in this work prepared via mannich reaction through various starting materials like ( furan , thiophene , benzothiazole derivatives ) with functional groups in terminals of compounds like ( hydroxyl group , carboxyl group ) ., our method involved reaction between diamine compounds with aromatic aldehyde. then identification of synthesized compounds via identification techniques ( FT.IR , H.NMR , Mass ) – spectrophotometric , studying of thermal behavior , studying of bioactivity behavior for our compounds toward types of bacteria ( bacteria of Mouth like ( Streptococcus Mutans , Streptococcus Salivarius ) . Keywords: three components, bacteria, activity.